2016
DOI: 10.1177/2373379916640549
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress and Health Outcomes Comparison of Faculty Teaching in Online, On-Ground, and Mixed Working Environments

Abstract: This quantitative cross-sectional comparative study used the National Institute for Occupational Safety and Health occupational stress model to determine if stress levels and associated health outcomes vary among university educators based on work environment. Occupational stress has been identified as the most damaging form of stress, leading to lost work hours, low productivity, numerous health issues, and high health care costs. This study used a survey of 1,000 university instructors within the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Blended classes have an additional value for the educators. In a study of undergraduate education, instructors who taught online or hybrid courses reported less stress than those teaching solely in-person classes (Cameron et al, 2016).…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Blended classes have an additional value for the educators. In a study of undergraduate education, instructors who taught online or hybrid courses reported less stress than those teaching solely in-person classes (Cameron et al, 2016).…”
Section: Lessons Learnedmentioning
confidence: 99%